Assessing the impact of current control on the thermal management performance of thermoelectric cooling systems. (16th December 2020) - Liu, Zhaoyang; Tang, Aikun; Shan, Chunxian; Yuan, Xuezhen; Li, Jianming
Summary: A battery thermal management system (BTMS) is essential for the longevity and thermal safety characteristics of batteries. In this study, a cooling system based on a thermoelectric cooling (TEC) unit is designed to improve the heat performance of a battery pack. The varied increase in cell temperatures under natural convection, liquid cooling, and TEC was compared to verify its feasibility, after which the authors carried out a current condition optimization strategy. The discharge performance of the battery at a discharge rate of 1C is studied under the conditions of equivalent, differential, and sectional currents. Under the equivalent current condition, it was determined that at the end of discharge, the temperature increase of the battery can be controlled at approximately 3.5°C when the working current of the semiconductor cooling unit is at 3.5 A compared to 0.5 A. When the differential current condition was adopted, the temperature difference of the battery pack was enhanced and maintained within a temperature of 5°C. Piecewise current was proposed based on the performance evaluation of BTMS in the equivalent and differential current conditions. The increase in temperature of the battery pack was just 1.5°C, and the values of the temperature difference in the battery pack and single battery remained within 5°C. Compared with the differential current condition, the maximum temperature increased only by 1°C at the discharge end, with its power consumption reduced by 63.4%. Abstract : Equivalent current condition and differential current condition can control the maximum temperature of the battery below the initial temperature, which leads to undercooling, but the piecewise current method can avoid the phenomenon and significantly reduce the temperature fluctuation.